Achenbach syndrome (paroxysmal finger hematoma). (August 2019) - Godoy, Alejandro; Tabares, Aldo Hugo
Achenbach syndrome (paroxysmal finger hematoma) refers to a condition in which a patient exhibits episodic pain and swelling in one or more digits along with the subsequent appearance of a hematoma on the palmar side of the proximal phalanges. Achenbach syndrome is a benign condition of unknown etiology in which prodromal symptoms, such as pain, tingling, and itching, may occur from minutes to hours before the color change appears. The subdermal bleeding usually stops spontaneously or after local pressure is applied. The color changes usually disappear within a few days, without permanent sequelae. The diagnosis of Achenbach syndrome is based strictly on its clinical features because the results of all routine investigations are usually normal. Physicians should become aware of this condition in order to advise their patients about its benign prognosis and to avoid unnecessary testing.